Method for avoiding shrinkage cracking of UHPC structural component in hardening process

Through the material optimization, mix ratio regulation and construction process optimization of UHPC structural components, a complete shrinkage and crack control system was established, which solved the problem of poor adaptability of the two groups of concrete, achieved the integrity and durability of the structure, reduced material costs and maintenance costs, and extended the service life of the structure.

CN119589806AActive Publication Date: 2025-03-11NANCHANG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411830071.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-11
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

Using two sets of concrete at different construction stages requires ensuring that their performance is adapted to each other. If not, there will be problems such as unsolid grouting and poor concrete bonding, which will affect the integrity and durability of the structure.

Method used

Through the optimization of the material optimization, mix ratio regulation and construction process of concrete, a complete UHPC structural component shrinkage and crack control system has been established. The specific steps include raw material selection and optimization, mix ratio improvement, structural design and adjustment of construction technology, ensuring the processing of raw materials and mix ratio of concrete, optimizing the water-adhesive ratio, and using post-pouring tape and prestressing technology to carry out layered casting and moisturizing maintenance.

Benefits of technology

The two groups of concrete have effectively solved the problems of poor adaptability and poor bonding, ensuring the integrity and durability of the structure, reducing material costs, significantly reducing the risk of shrinkage and cracking of UHPC structural components during hardening, improving the quality and durability of the components, reducing maintenance and reinforcement costs, and extending the service life of the structure.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for avoiding shrinkage cracking of a UHPC structural member in the hardening process. The method aims at solving the problems that grouting is not compact and concrete combination is poor when two sets of concrete are used in different construction stages and are not matched. The method comprises the following steps: S1, carrying out concrete performance test on concrete samples of different gradation, and determining optimized gradation aggregate through the concrete performance test; s2, determining a concrete raw material ratio and an optimal water-binder ratio; s3, when the UHPC structural member is installed, a post-cast strip and a prestress technology are adopted for assistance, the tensioning force of the prestressed steel bars is increased according to the total prestress loss value F, and it is ensured that prestress can be effectively transmitted to a concrete structure; and S4, layered pouring is conducted on the installed UHPC structural component. By selecting and optimizing the raw materials and adjusting the construction technology, the construction precision during structure installation and pouring can be guaranteed, and the shrinkage cracking risk of the UHPC structural component in the hardening process is remarkably reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ultra-high performance concrete prefabricated component manufacturing, and in particular relates to a method for preventing shrinkage and cracking of UHPC structural components during hardening. Background Art

[0002] UHPC (ultra-high performance concrete) has the advantages of high strength and high durability, but it is prone to shrinkage cracking during the hardening process, which not only affects the appearance and performance of the components, but may also reduce their service life.

[0003] For example, Chinese patent CN110027109A discloses a method for avoiding shrinkage and cracking of UHPC structural components during the hardening process. When pouring UHPC, a hole is reserved, and the stress-bearing steel bars are arranged after the UHPC hardens, thereby reducing the uncoordinated deformation of concrete and internal steel caused by concrete shrinkage. Whether to apply prestress is selected according to needs, and finally the reserved hole is grouted and cured to complete the production of the component.

[0004] In the above method, although the problem of shrinkage cracks that are prone to occur during the hardening process of UHPC structural components is solved by reserving channels and stress-bearing steel bars, two groups of ultra-high performance concrete are used. The two groups of concrete are used in different construction stages, and it is necessary to ensure that the performance of the two groups is compatible with each other, including fluidity, setting time, strength development and other aspects. If they are not compatible, problems such as loose grouting and poor concrete bonding will occur, affecting the integrity and durability of the structure. Summary of the invention

[0005] The purpose of the present invention is to solve the problem of using two groups of concrete in different construction stages, and to ensure that the performance of the two groups is compatible with each other, including fluidity, setting time, strength development and other aspects. If they are not compatible, problems such as loose grouting and poor concrete bonding will occur, affecting the integrity and durability of the structure, thereby providing a method for avoiding shrinkage and cracking of UHPC structural components during the hardening process.

[0006] The method of the present invention for avoiding shrinkage cracking of UHPC structural components during hardening is implemented by the following steps:

[0007] S1. Raw material selection and optimization:

[0008] Mixing cement and aggregates of different continuous gradations to prepare multiple groups of concrete samples, performing concrete performance tests on the concrete samples of different gradations, determining the optimized gradation aggregate through the concrete performance test, and mixing cement, the optimized gradation aggregate and additives to obtain a mixed raw material;

[0009] S2. Improvement of mix ratio:

[0010] The mixed raw materials, water, silica fume and fly ash are stirred and mixed to prepare multiple groups of concrete specimens with different water-binder ratios, and the concrete density of the concrete specimens is tested to determine the optimal water-binder ratio, and to determine the concrete raw material ratio and the optimal water-binder ratio;

[0011] S3. Optimize structural design:

[0012] When installing UHPC structural components, post-casting strips and prestressing processes are used for assistance. The width of the post-casting strips is set to 850-1200mm. Prestressed steel bars and anchors are used in the prestressing process. The total prestress loss is calculated based on the relaxation of prestressed steel bars, the shrinkage and creep of concrete on the prestress. The calculation formula for the total prestress loss value is as follows:

[0013] F=F l1 +F l2 +F l3 +F l4 +F l5 ;

[0014] In the formula, F l1 is the prestress loss caused by anchor deformation and prestressed steel bar shrinkage, F l2 is the prestress loss caused by friction between the prestressed steel bars and the hole wall, F l3 The prestress loss caused by the temperature difference between the tensioned steel bars and the equipment bearing the tension during concrete heating and curing, F l4 is the prestress loss caused by stress relaxation of prestressed steel bars, F l5 The prestress loss caused by shrinkage and creep of concrete;

[0015] According to the total prestress loss value F, the tensioning force of the prestressed steel bars is increased to compensate for the prestress loss. After the prestressed steel bars are tensioned, they are anchored with anchors to ensure that the prestress is effectively transferred to the concrete structure, thereby obtaining the installed UHPC structural components;

[0016] S4. Adjust the construction process:

[0017] According to step S2, the concrete raw material ratio and the optimal water-binder ratio are determined to configure the concrete raw materials, and the installed UHPC structural components are cast in layers using the concrete raw materials. The lower layer of concrete is cast first and vibrated. When the lower layer of concrete is initially set but not completely hardened, the surface of the lower layer of concrete is brushed and chiseled, and then the upper layer of concrete is cast and vibrated. After the casting is completed, moisturizing maintenance is performed, and the entire UHPC structure is protected by a wrapping method, thereby completing the method for avoiding shrinkage and cracking of UHPC structural components during the hardening process.

[0018] The present invention establishes a complete shrinkage cracking control system for UHPC structural components by optimizing concrete materials, adjusting mix ratios and optimizing construction processes, effectively solving the problems of poor compatibility and poor bonding between two groups of concrete in the prior art.

[0019] Compared with the prior art, the method of the present invention for avoiding shrinkage cracking of UHPC structural components during hardening process includes the following beneficial effects:

[0020] In the present invention, the raw materials and mix ratio of concrete can be processed by selecting and optimizing raw materials and improving mix ratio, so as to ensure the coordination and unity of the performance of two groups of UHPC, reduce the interference of adaptability, avoid the problems of loose grouting and poor concrete bonding, and ensure the integrity and durability of the structure; by optimizing the structural design and adjusting the construction process, the construction accuracy during structural installation and pouring can be guaranteed, thereby improving the construction accuracy control level and ensuring the quality and safety of structural components; reducing material costs, significantly reducing the risk of shrinkage cracking of UHPC structural components during the hardening process, improving the quality and durability of components, reducing maintenance and reinforcement costs, and extending the service life of the structure. DETAILED DESCRIPTION

[0021] Specific implementation method 1: The method of avoiding shrinkage cracking of UHPC structural components during hardening in this implementation method is implemented according to the following steps:

[0022] S1. Raw material selection and optimization:

[0023] Mixing cement and aggregates of different continuous gradations to prepare multiple groups of concrete samples, performing concrete performance tests on the concrete samples of different gradations, determining the optimized gradation aggregate through the concrete performance test, and mixing cement, the optimized gradation aggregate and additives to obtain a mixed raw material;

[0024] S2. Improvement of mix ratio:

[0025] The mixed raw materials, water, silica fume and fly ash are stirred and mixed to prepare multiple groups of concrete specimens with different water-binder ratios, and the concrete density of the concrete specimens is tested to determine the optimal water-binder ratio, and to determine the concrete raw material ratio and the optimal water-binder ratio;

[0026] S3. Optimize structural design:

[0027] When installing UHPC structural components, post-casting strips and prestressing processes are used for assistance. The width of the post-casting strips is set to 850-1200mm. Prestressed steel bars and anchors are used in the prestressing process. The total prestress loss is calculated based on the relaxation of prestressed steel bars, the shrinkage and creep of concrete on the prestress. The calculation formula for the total prestress loss value is as follows:

[0028] F=F l1 +Fl2 +F l3 +F l4 +F l5 ;

[0029] In the formula, F l1 is the prestress loss caused by anchor deformation and prestressed steel bar shrinkage, F l2 is the prestress loss caused by friction between the prestressed steel bars and the hole wall, F l3 The prestress loss caused by the temperature difference between the tensioned steel bars and the equipment bearing the tension during concrete heating and curing, F l4 is the prestress loss caused by stress relaxation of prestressed steel bars, F l5 The prestress loss caused by shrinkage and creep of concrete;

[0030] According to the total prestress loss value F, the tensioning force of the prestressed steel bars is increased to compensate for the prestress loss. After the prestressed steel bars are tensioned, they are anchored with anchors to ensure that the prestress is effectively transferred to the concrete structure, thereby obtaining the installed UHPC structural components;

[0031] S4. Adjust the construction process:

[0032] According to step S2, the concrete raw material ratio and the optimal water-binder ratio are determined to configure the concrete raw materials, and the installed UHPC structural components are cast in layers using the concrete raw materials. The lower layer of concrete is cast first and vibrated. When the lower layer of concrete is initially set but not completely hardened, the surface of the lower layer of concrete is brushed and chiseled, and then the upper layer of concrete is cast and vibrated. After the casting is completed, moisturizing maintenance is performed, and the entire UHPC structure is protected by a wrapping method, thereby completing the method for avoiding shrinkage and cracking of UHPC structural components during the hardening process.

[0033] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the concrete performance test in step S1 includes a shrinkage test and a strength test.

[0034] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that in step S1, isobutyl triethoxysilane is used to impregnate the optimized graded aggregate for surface treatment.

[0035] This embodiment adopts the silane impregnation method to modify the aggregate surface, so that the silane molecules form a dense molecular film on the aggregate surface. This molecular film not only forms a chemical bond with the aggregate surface, but also produces good physical adsorption with the cement hydration product, thereby significantly enhancing the structure of the interface transition zone at the microscopic level and improving the overall performance of the concrete.

[0036] This embodiment uses isobutyl triethoxysilane, which has good permeability and can penetrate into the pores of aggregates. The chemical structure of isobutyl triethoxysilane enables it to react with the hydroxyl groups on the surface of aggregates after hydrolysis to form a strong chemical bond, thereby effectively improving the performance of aggregates. In the aggregate treatment of some high-performance concretes, the use of silane materials can enhance the bonding force between aggregates and cement paste.

[0037] Specific embodiment 4: This embodiment is different from specific embodiment 3 in that the time for impregnating the optimized graded aggregate with isobutyl triethoxysilane is 2-4 hours at a temperature of 20-30°C.

[0038] Specific implementation method five: This implementation method is different from any one of specific implementation methods one to four in that the additive in step S1 is one or more of a water reducing agent, an expansion agent and a shrinkage reducing agent.

[0039] Specific implementation method six: This implementation method is different from specific implementation methods one to five in that the optimal water-binder ratio of concrete is determined to be in the range of 0.10-0.21 in step S2.

[0040] In step S2 of this embodiment, the preferred water-binder ratio of concrete is determined to be in the range of 0.15-0.20.

[0041] Specific embodiment 7: This embodiment is different from the specific embodiments 1 to 6 in that the total amount of the gel material composed of cement, silica fume and fly ash in the concrete raw materials is determined to be 800-1300 kg / m 3 .

[0042] The total amount of gel material in this embodiment is preferably 1000-1200 kg / m 3 .

[0043] This embodiment measures the initial water-binder ratio of the mixed raw materials (including cement, silica fume, fly ash, etc.) obtained in step S1, divides these raw materials into 5 groups, adjusts the water-binder ratio of each group in turn, tests the adjusted concrete density, determines the optimal water-binder ratio based on the test results, and then adjusts the amount of gel material based on the ratio.

[0044] Specific implementation eight: This implementation differs from any one of specific implementations one to seven in that in step S3, the spacing of the post-cast strips is controlled to be 20-45m, and the retention time of the post-cast strips is 50-65 days.

[0045] Specific implementation method 9: The difference between this implementation method and specific implementation methods 1 to 8 is that in step S4, the pouring temperature of the upper concrete and the lower concrete is controlled between 10-25° C., and the pouring speed is 3-5 cubic meters per hour.

[0046] Specific embodiment ten: This embodiment is different from specific embodiments one to nine in that a wrapping method is used in step S4 to protect the entire UHPC structure, and the wrapping material is a plastic film, a geotextile or an insulation board.

[0047] This implementation method selects wrapping materials such as plastic film, geotextile or insulation board, as well as tools such as scissors, tape, and rope according to the component requirements and environment. Clean the surface of the component, cut the material according to its size and shape, and carry out the wrapping operation. For example, when wrapping with plastic film, put the component in the middle and pull up the edges to seal it in turn. After wrapping with geotextile, use ropes to reinforce it. If there is a need for multiple layers of wrapping, proceed in sequence. Check the effect after wrapping, regularly check and maintain during use, and repair or replace damaged wrapping materials in time to ensure that UHPC structural components are effectively protected.

[0048] Embodiment 1: The method for avoiding shrinkage cracking of UHPC structural components during hardening in this embodiment is implemented according to the following steps:

[0049] S1. Raw material selection and optimization:

[0050] Cement is mixed with aggregates of different continuous gradations. The selection criteria of coarse aggregates during gradation are high strength and good particle shape. Natural sand and machine-made sand are used as fine aggregates. Multiple groups of concrete samples are prepared. Concrete performance tests are performed on concrete samples of different gradations. The concrete performance tests include shrinkage tests and strength tests. The experimental data are analyzed, and attention is paid to the particle distribution. If the particle content in a certain particle size range is unreasonable, it needs to be adjusted. Attention is paid to the void ratio data. If the void ratio is high, the particle collocation should be optimized to reduce it. The performance test results are referred to. If the strength does not meet the standard, the gradation needs to be improved. The optimized gradation aggregate is determined through the concrete performance test. The cement (in this embodiment, P·O 2 is selected) is mixed with cement and the particle distribution is adjusted. 52.5 grade silicate cement), optimized graded aggregate and additives (water reducer, expansion agent and shrinkage reducer) are mixed to obtain a mixed raw material; wherein the mass ratio of coarse aggregate to fine aggregate is 3:7, the coarse aggregate is composed of crushed stones with particle sizes of 1.18-2.36mm, 2.36-4.75mm and 4.75-9.5mm in a mass ratio of 4:3:3, and the fine aggregate is composed of quartz sand with particle sizes of 0.15-0.3mm, 0.3-0.6mm and 0.6-1.18mm in a mass ratio of 1:1:1;

[0051] The gradation and proportion of the coarse aggregate and fine aggregate in this embodiment are determined by concrete performance testing;

[0052] In this embodiment, both the coarse aggregate and the fine aggregate are impregnated with isobutyl triethoxysilane at a temperature of 25°C for 2.5 hours;

[0053] S2. Improvement of mix ratio:

[0054] The mixed raw materials, water, silica fume and fly ash were stirred and mixed to prepare 5 groups of concrete specimens with different water-binder ratios. The concrete density of the concrete specimens was tested, and the optimal water-binder ratio was determined according to the test results. The amount of gel material was adjusted according to the ratio to determine the concrete raw material ratio and the optimal water-binder ratio. The water-binder ratio of UHPC in this embodiment was 0.10, and the gel material included cement, silica fume and fly ash. The total amount of gel material was 800 kg / m 3 ;

[0055] S3. Optimize structural design:

[0056] When installing UHPC structural components, post-casting strips and prestressing processes are used for assistance. The width of the post-casting strips is set to 850mm, the spacing is 20m, and the retention time of the post-casting strips is 50 days. Prestressed steel bars and anchors are used in the prestressing process. According to the relaxation of prestressed steel bars, the shrinkage and creep of concrete on the prestress, the total prestress loss is calculated. The calculation formula of the total prestress loss value is as follows:

[0057] F=F l1 +F l2 +F l3 +F l4 +F l5 ;

[0058] In the formula, F l1 is the prestress loss caused by anchor deformation and prestressed steel bar shrinkage, F l2 is the prestress loss caused by friction between the prestressed steel bars and the hole wall, F l3 The prestress loss caused by the temperature difference between the tensioned steel bars and the equipment bearing the tension during concrete heating and curing, F l4 is the prestress loss caused by stress relaxation of prestressed steel bars, F l5 The prestress loss caused by shrinkage and creep of concrete;

[0059] After calculating the prestress loss, the following processing is required:

[0060] (1) According to the calculated total prestress loss value, the initial tension force is increased accordingly to compensate for the expected prestress loss;

[0061] (2) The prestressed tendons are tensioned in stages, with each stage tensioning force not exceeding 25% of the design tensioning force;

[0062] (3) After reaching the designed tension force, keep the tension force stable for a certain period of time (15-20 minutes) and observe whether the elongation value of the prestressed tendon is stable;

[0063] (4) Record the actual tension and elongation values ​​and compare them with the theoretical calculated values ​​to ensure that the deviation is within the allowable range (no more than ±6%);

[0064] (5) If the deviation exceeds the allowable range, analyze the cause and take appropriate measures, and re-tension if necessary;

[0065] (6) After the tensioning is completed, the prestressed tendons are anchored in time to ensure that the prestress is effectively transferred to the concrete structure and the installed UHPC structural components are obtained;

[0066] S4. Adjust the construction process:

[0067] According to step S2, the concrete raw material ratio and the optimal water-binder ratio are determined to configure the concrete raw materials, and the installed UHPC structural components are cast in layers using the concrete raw materials. The lower layer of concrete (half of the total thickness) is cast first and vibrated. When the lower layer of concrete is initially set but not completely hardened, the surface of the lower layer of concrete is brushed and chiseled, and then the upper layer of concrete is cast and vibrated. After the casting is completed, moisturizing maintenance is performed, and the entire UHPC structure is protected by a wrapping method, thereby completing the method of avoiding shrinkage and cracking of UHPC structural components during the hardening process.

[0068] In this example, the water-binder ratio of UHPC is relatively low, the total amount of gel material is small, the density of the concrete after testing is low, the porosity in the cement stone is high, the workability of the concrete is deteriorated, and the construction quality is affected.

[0069] Example 2: The difference between this example and Example 1 is that the water-binder ratio of UHPC in step S2 is 0.15, the gel material includes cement, silica fume and fly ash, and the total amount of gel material is 1100 kg / m 3 ;

[0070] In step S3, when installing UHPC structural components, post-cast strips and prestressing processes are used to assist. The width of the post-cast strips is set to 1100 mm, the spacing is 30 m, and the retention time of the post-cast strips is 58 days. Prestressed steel bars and anchors are used in the prestressing process. The total prestress loss is calculated based on the relaxation of the prestressed steel bars, the shrinkage of concrete, and the influence of creep on the prestress.

[0071] In this embodiment, the water-cement ratio of UHPC is 0.15, the total amount of gel material is moderate, the density of concrete is high, and the porosity in cement stone is low, thereby reducing the space for water evaporation and shrinkage, and ensuring the workability and construction quality of concrete.

[0072] Example 3: The difference between this example and Example 1 is that the water-binder ratio of UHPC in step S2 is 0.21, the gel material includes cement, silica fume and fly ash, and the total amount of gel material is 1300kg / m 3 ;

[0073] In step S3, when installing UHPC structural components, post-cast strips and prestressing processes are used for assistance. The width of the post-cast strips is set to 1200 mm, the spacing is 45 m, and the retention time of the post-cast strips is 65 days. Prestressed steel bars and anchors are used in the prestressing process. The total prestress loss is calculated based on the relaxation of the prestressed steel bars, the shrinkage and creep of the concrete on the prestress.

[0074] In this embodiment, the water-cement ratio of UHPC is 0.21, the total amount of gel material is moderate, the density of concrete is slightly lower than that in Example 2, and the porosity in the cement stone is higher than that in Example 2, which increases the space for water evaporation and shrinkage. Compared with Example 2, the workability and construction quality of the concrete are reduced.

[0075] In the present invention, the raw materials and mix ratio of concrete can be processed by selecting and optimizing raw materials and improving mix ratio, optimizing the water-cement ratio, ensuring the coordination and unity of the performance of two groups of UHPC, reducing the interference of adaptability, avoiding the problems of loose grouting and poor concrete bonding, and ensuring the integrity and durability of the structure; by optimizing the structural design, the UHPC structural components are assisted by post-casting strips and prestressing technology, and the post-casting strips can allow the concrete to shrink freely in the early stage and reduce the restraining stress. By applying prestress to the structural components, the tensile stress generated by the concrete during the hardening process can be offset, thereby preventing shrinkage cracking;

[0076] The use of layered pouring can reduce the one-time pouring amount of concrete and reduce shrinkage stress. During the pouring process, the pouring speed and pouring sequence are strictly controlled to ensure the uniformity and density of the concrete. By strengthening the vibration control and adopting appropriate vibration equipment and vibration methods, the concrete can be fully compacted. Over-vibration or missed vibration should be avoided during the vibration process to prevent quality problems such as segregation or honeycomb surface of the concrete. The construction accuracy during structural installation and pouring can be guaranteed, thereby improving the level of construction accuracy control and ensuring the quality and safety of structural components; reducing material costs, significantly reducing the risk of shrinkage cracking of UHPC structural components during the hardening process, improving the quality and durability of components, reducing maintenance and reinforcement costs, and extending the service life of the structure.

[0077] The present invention proposes a systematic mix ratio optimization method. By dividing the raw materials into 5 groups for parallel testing, a relationship curve between the water-binder ratio and the density of concrete is established, and the optimal mix ratio is accurately determined. The optimal distribution of hydration products is achieved in the microstructure, which not only ensures the good workability of the concrete, but also effectively controls the shrinkage deformation.

[0078] The present invention realizes integration in construction technology. By controlling the thickness of each layer in the layered casting to half of the total thickness, this optimal ratio is determined based on the study of the fluidity and shrinkage characteristics of UHPC materials. At the same time, a composite treatment method of brushing and chiseling is adopted to form a transition layer with a specific roughness at the microscopic level, which significantly improves the interlayer bonding strength. In terms of maintenance, a combination of moisturizing maintenance and wrapping is adopted to control the water evaporation rate and ensure the uniformity of maintenance.

[0079] The present invention establishes a complete prestress loss calculation and compensation system. By comprehensively considering multiple factors such as anchor deformation, prestressed steel bar shrinkage, friction loss, and providing a specific compensation scheme, the durability of the prestressing effect is ensured. This systematic compensation method, combined with construction process control, significantly improves the application effect of prestressing technology in UHPC structural components.

[0080] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for avoiding shrinkage cracking of UHPC structural components during hardening, characterized in that The method for avoiding shrinkage cracking of UHPC structural components during hardening is achieved by the following steps: S1. Raw material selection and optimization: Mixing cement and aggregates of different continuous gradations to prepare multiple groups of concrete samples, performing concrete performance tests on the concrete samples of different gradations, determining the optimized gradation aggregate through the concrete performance test, and mixing cement, the optimized gradation aggregate and additives to obtain a mixed raw material; S2. Improvement of mix ratio: The mixed raw materials, water, silica fume and fly ash are stirred and mixed to prepare multiple groups of concrete specimens with different water-binder ratios, and the concrete density of the concrete specimens is tested to determine the optimal water-binder ratio, and to determine the concrete raw material ratio and the optimal water-binder ratio; S3. Optimize structural design: When installing UHPC structural components, post-casting strips and prestressing processes are used for assistance. The width of the post-casting strips is set to 850-1200mm. Prestressed steel bars and anchors are used in the prestressing process. The total prestress loss is calculated based on the relaxation of prestressed steel bars, the shrinkage and creep of concrete on the prestress. The calculation formula for the total prestress loss value is as follows: F=F l1 +F l2 +F l3 +F l4 +F l5 ; In the formula, F l1 is the prestress loss caused by anchor deformation and prestressed steel bar shrinkage, F l2 is the prestress loss caused by friction between the prestressed steel bars and the hole wall, F l3 The prestress loss caused by the temperature difference between the tensioned steel bars and the equipment bearing the tension during concrete heating and curing, F l4 is the prestress loss caused by stress relaxation of prestressed steel bars, F l5 The prestress loss caused by shrinkage and creep of concrete; According to the total prestress loss value F, the tensioning force of the prestressed steel bars is increased to compensate for the prestress loss. After the prestressed steel bars are tensioned, they are anchored with anchors to ensure that the prestress is effectively transferred to the concrete structure, thereby obtaining the installed UHPC structural components; S4. Adjust the construction process: According to step S2, the concrete raw material ratio and the optimal water-binder ratio are determined to configure the concrete raw materials, and the installed UHPC structural components are poured in layers. The lower layer of concrete is poured first and vibrated. When the lower layer of concrete is initially set but not completely hardened, the surface of the lower layer of concrete is brushed and chiseled, and then the upper layer of concrete is poured and vibrated. After the pouring is completed, moisturizing maintenance is performed, and the entire UHPC structure is protected by a wrapping method, thereby completing the method for avoiding shrinkage and cracking of UHPC structural components during the hardening process.

2. The method for avoiding shrinkage cracking of UHPC structural components during hardening according to claim 1, characterized in that The concrete performance test in step S1 includes a shrinkage test and a strength test.

3. The method for avoiding shrinkage cracking of UHPC structural components during hardening according to claim 1, characterized in that In step S1, isobutyltriethoxysilane is used to impregnate the optimized graded aggregate for surface treatment.

4. The method for avoiding shrinkage cracking of UHPC structural components during hardening according to claim 3, characterized in that The time for impregnating the optimized graded aggregate with isobutyltriethoxysilane is 2-4 hours at a temperature of 20-30°C.

5. The method for avoiding shrinkage cracking of UHPC structural components during hardening according to claim 1, characterized in that The additives described in step S1 are one or more of a water reducing agent, an expansion agent and a shrinkage reducing agent.

6. The method for avoiding shrinkage cracking of UHPC structural components during hardening according to claim 1, characterized in that In step S2, the optimal water-cement ratio of concrete is determined to be in the range of 0.15-0.

20.

7. The method for avoiding shrinkage cracking of UHPC structural components during hardening according to claim 1, characterized in that In step S2, the total amount of the gel material composed of cement, silica fume and fly ash in the concrete raw materials is determined to be 800-1300 kg / m 3 .

8. The method for avoiding shrinkage cracking of UHPC structural components during hardening according to claim 1, characterized in that In step S3, the spacing of the post-cast strips is controlled to be 20-45m, and the retention time of the post-cast strips is 50-65 days.

9. The method for avoiding shrinkage cracking of UHPC structural components during hardening according to claim 1, characterized in that In step S4, the pouring temperature of the upper concrete and the lower concrete is controlled to be between 10-25° C., and the pouring speed is 3-5 cubic meters per hour.

10. The method for avoiding shrinkage cracking of UHPC structural components during hardening according to claim 1, characterized in that In step S4, the entire UHPC structure is protected by a wrapping method, and the wrapping material is selected from plastic film, geotextile or insulation board.

Citation Information

Patent Citations

  • Method for preventing shrinkage cracking of UHPC structural member in hardening process

    CN110027109A

  • Method for comprehensively preventing and treating indirect cracks in premixed concrete construction periods

    CN103669871A

  • Assembled permanent formwork overlapped FRP rib seawater sea sand recycled concrete beam and manufacturing method thereof

    CN110318495A

  • Ultra-long concrete construction crack control method

    CN110965655A

  • Construction process of prefabricated prestressed hollow slab beam

    CN118952447A